Engaging Men as Fathers: How Gender Influences Men's Involvement in Australian Family Health Services. (November 2018) - Pfitzner, Naomi; Humphreys, Cathy; Hegarty, Kelsey
Despite claims of "new" and "involved" fathers, research shows men's actual fathering practices remain relatively unchanged. Increasing attention is being paid to the influence of child and family services on father engagement with calls from researchers and practitioners for a game change in parenting interventions. In this article, we draw on case study data to examine how gender impacts on maternal and child health services' engagement with new fathers in respectful relationships programs. Our analysis shows that gender shapes men's fathering and consequently their involvement in programs that seek to engage men as fathers. These gendered behaviors intersect with the practices, policies, and orientation of the Maternal and Child Health Service. The findings hold important implications for designing strategies to engage men in family services.